Impact evaluation baseline survey of school dormitory environment in Mongolia. ([Manila] Asian Development Bank, 2019)
It describes the methodology of the impact evaluation and discusses the findings of the baseline survey of dormitories, schools, and circumstances surrounding survey respondents during the school year 20162017. The survey also covered school attendance, levels of participation in study, reading and extracurricular activities, and 5th grade test scores among primary students living in dormitories. Recommendations are provided for preparing an endline survey to measure impacts of the grant project in the school year 20202021.
Keywords: Interdisciplinary approach in education -- Mongolia; Education, Secondary -- Curricula -- Mongolia; Electronic books